Koncentrace kyseliny hyaluronové v synoviální tekutině jako ukazatel závažnosti a stupně postižení u pacientů s gonartrózou - Kotaška, Jan; Hanousková, Lenka; Průša, Richard; Trč, Tomáš; Kotaška, Karel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2021)
PURPOSE OF THE STUDY Hyaluronic acid is a major component of synovial fluid and an indicator of joint viscosity and viscoelasticity. Decreased concentrations of hyaluronic acid in the synovial fluid indicate the severity of osteoarthritis. The aim of the study was to determine the concentrations of hyaluronic acid in the synovial fluid and to evaluate the correlation with the severity of osteoarthritis determined based on the radiological criteria (evaluation according to X-ray classification) and the physicochemical criteria (measurement of synovial fluid osmolality). MATERIAL AND METHODS A total of 67 patients with the mean age of 67 years (35 men, mean age = 65 years, and 32 women, mean age = 68 years) with clinically diagnosed osteoarthritis were included in the study. The patients were divided into four groups according to the severity of arthrosis (from Group 1 - the lowest degree of disability to Group 4 - the most severe degree of arthrosis). Samples were taken during knee arthroscopies or total knee replacements. Hyaluronic acid concentrations in synovial fluid were determined using a commercially available kit based on the sandwich ELISA principle (Teco Hyaluronic acid, Switzerland). Osmolality was measured by the cryoscopic method. RESULTS The average concentrations of hyaluronic acid in the synovial fluid in the individual groups were as follows: Group 1: HA = 2302 mg/L, Group 2: HA = 2234 mg/L, Group 3: HA = 2300 mg/L, Group 4: HA = 2446 mg/L. HA concentrations in synovial fluid did not differ from the published reference values in synovial fluid (1500 - 3200 mg/L. HA concentrations do not depend on age, sex, and severity of the disease. The patients who underwent arthroscopy have significantly elevated synovial HA concentration compared to the patients who underwent total knee replacements (2581 mg/l/L vs. 1763 mg/l/L, p = 0.01, Mann-Whitney test). HA positively correlates with the osmotic pressure determined by the examination of osmolality in synovial fluid (r = 0.29, p = 0.015). CONCLUSIONS Hyaluronic acid concentrations in patients with knee osteoarthritis who underwent arthroscopy are significantly increased compared to the group of patients with total knee replacement. Hyaluronic acid concentrations in the synovial fluid correlate with the increased osmotic pressure, and may therefore be an additional indicator of the severity of the disease. Key words: hyaluronic acid, knee arthrosis, total knee replacement, osmolality.
Keywords: kyselina hyaluronová; Hyaluronic Acid; artróza kolenních kloubů; lidé; Knee Joint; Aged; Humans; Arthroplasty, Replacement, Knee; senioři; totální endoprotéza kolene; mužské pohlaví; kolenní kloub; synoviální tekutina; Male; Osteoarthritis, Knee; Synovial Fluid; ženské pohlaví; Female